THE PREVALENCE OF INSOMNIA AND ASSOCIATED FACTORS AMONG OUTPATIENTS WITH CHRONIC OBSTRUCTIVE PULMONARY DISEASE AT THE NATIONAL LUNG HOSPITAL IN 2025 (Vietnam Journal of Community Medicine, 2026)
Objective: This study aimed to assess the prevalence of insomnia and identify factors associated with insomnia among outpatients with chronic obstructive pulmonary disease (COPD) at the National Lung Hospital in 2025.Methods: A cross-sectional study was conducted on 302 COPD outpatients from April to June 2025, and insomnia was assessed using the Insomnia Severity Index (ISI).Results: The findings showed that 67.9% of patients experienced insomnia at varying degrees. The most common symptoms were difficulty falling asleep (93.7%), difficulty maintaining sleep (93.3%), and early morning awakening (92.3%). The mean ISI score was 12.7 ± 5.9. Several factors were significantly associated with insomnia, including age, gender, regular exercise, the number of exacerbations and hospitalizations in the past year, comorbid chronic diseases, and the use of home oxygen therapy and ventilatory support.Conclusion: The prevalence of insomnia among COPD outpatients was relatively high, highlighting the need for routine screening and assessment of sleep disturbances as part of comprehensive COPD management to improve patients’ overall health and quality of life.
Keywords: Insomnia; Chronic obstructive pulmonary disease; COPD outpatients; Insomnia Severity Index